Perbedaan Lama dan Jenis Persalinan pada Ibu Bekerja Berdasarkan Keikutsertaan Senam Hamil - Hermin Yulianti; Fariani Syahrul (Universitas Airlangga, 2017)
Working during pregnancy has negative effect for the health status of pregnant women. Exercises during pregnancy is one of the ways to improve the health status of pregnant women. The aim of research was to analyze the differences of duration and type of childbirth based on the exercises during pregnancy on working mother. This research was an observational analytic study with retrospective cohort design. The exposed population was third trimester of pregnant women who worked and participated in pregnancy exercises > 180 minutes. The non-exposed population was third trimester of pregnant women who worked and participated in pregnancy exercises ≤ 180 minutes. Sample for the exposed group was 30 pregnant women and the non-exposed group was 60 pregnant women. The research analysis was to find the RR value with 95% Confidence Interval (CI). Pregnant women who participated in pregnancy exercises have a short or normal childbirth period 1.543 times than non-participated women. Pregnant women who participated in pregnancy exercises have a normal type of childbirth 1.256 times than non-participated women. There were differences of duration and type of childbirth based on the pregnancy exercises on working mother.